Inpatient Case-mix Cost Vs Average Cost for Health Care Services in King Fahd Central Hospital, Saudi Arabia: A Comparative Study - Asim, Mehmood; Zafar, Ahmed; Khalid, Ghilan; Ahmed, Damad; Fahad Khan, Azeez (SAGE Journals, 2021)
Health care systems aim to deliver high-quality medical care while considering efficient resource usage and cost-effective forms of interventions. Such purposes require scientific tools or mechanisms which aid in cost assessment before the efforts of cost reduction are considered. Diagnosis-related groups based costing methodology (Case-mix) is considered one of the preferred costing approaches in the health care sector. King Fahd Central hospital Jazan, the only tertiary hospital in the Jazan region, was selected for case-mix system-based patient-level costing of health services. The study’s objective was to estimate the cost per Diagnosis-Related Group (DRG) per inpatient admission and compare it with the already established average cost of health care services for inpatients. We applied a cross-sectional retrospective approach to categorize the inpatients based on their diagnosis and procedures and then estimate the actual cost of health care services provided to inpatients during 2018 and compared it with the average cost of the health services. There was a considerable difference between DRG-based costing (SAR 269,663,897) and average costing (SAR 247,035,938). The Diagnosis Related Group costing was found to be more reliable and representative of the services provided to the patients and is recommended to be used for reimbursement purpose.